Il reclamo e la mediazione tra procedimento e processo - Parente, Salvatore Antonello (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The complaint/mediation, symptomatic of the evolution of the regulatory system towards a “marginalization” of the litigation phase, is located in the phase preceding the taxation process. For disputes covered by tax jurisdiction whose value does not exceed € 20,000.00, the submission of a claim is required – for the purpose of the applicability of the claim – to contain a proposal of mediation intended to prevent the onset of the legal proceedings; in case of failure to accept the claim or the mediation proposal, the taxation is applied. From an objective point of view, the obligation of the prior exercise of the complaint concerns only the disputes that fall within the tax jurisdiction. From the subjective point of view, the scope of application of the mediation/complaint concerns all disputes within the tax jurisdiction, which concern the appeal of acts and measures provided by any type of taxpayer. The body competent to know the procedure belongs to the same authority that issued the contested measure, thus different and autonomous structures from those who have investigated the acts of reclamation are involved.